Analytical solutions for circular composite-lined tunnels under obliquely incident seismic SV and P waves. (November 2022) - Zhao, Mi; Duan, Yawei; Huang, Jingqi; Li, Huifang; Zhao, Xu; Du, Xiuli
Abstract: An analytical solution can easily and quickly give the internal forces in tunnels due to seismic waves, by which, the relationship between the key parameters could also be clarified. These methods are widely used in preliminary seismic design of tunnels. This paper presents new analytical solutions for thrust and moment of circular composite-lined tunnels with arbitrary layer linings under obliquely incident SV waves and P waves. Wherein, the lining is regarded as a thick-wall cylinder. Moreover, the proposed analytical solutions can consider different contact conditions of the ground-tunnel and lining-lining interface. The new analytical solutions are verified by comparing with the dynamic finite element analysis results. The results show the accuracy and applicability of the proposed analytical solutions. Parametric analyses are performed to explore the effects of the flexibility coefficient δ, incident angle and steel lining on the seismic response of tunnels.